Epigenetics and Testicular Cancer: Bridging the Gap Between Fundamental Biology and Patient Care - Nicu, Alina-Teodora; Medar, Cosmin; Chifiriuc, Mariana Carmen; Gradisteanu Pircalabioru, Gratiela; Burlibasa, Liliana (Frontiers in Cell and Developmental Biology, 2022)
Testicular cancer is the most common solid tumor affecting young males. Most testicular cancers are testicular germ cell tumors (TGCTs), which are divided into seminomas (SGCTs) and non-seminomatous testicular germ cell tumors (NSGCTs). During their development, primordial germ cells (PGCs) undergo epigenetic modifications and any disturbances in their pattern might lead to cancer development. The present study provides a comprehensive review of the epigenetic mechanisms - DNA methylation, histone post-translational modifications, bivalent marks, non-coding RNA associated with TGCT susceptibility, initiation, progression and response to chemotherapy. Also, an important purpose of this review is to highlight the recent investigations regarding the identification and development of epigenetic biomarkers as powerful tools for the diagnostic, prognostic and especially for epigenetic-based therapy.